Pengaruh Work Family Conflict Dan Beban Kerja Terhadap Kinerja Karyawan Wanita Di Usaha Kecil Dan Menengah Desa Bringin Kecamatan Juwana Kabupaten Pati - Indah Novita Sari (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2022)
This study aims to idetermine the effect of work ifamily iconflict and workload on the iperformance of female iemployees in Small and Medium Enterprises, Bringin Village, Juwana District, Pati Regency. This research was conducted on married female employees in Bringin Village. The population of this study were 99 female employees who worked in Small and Medium Enterprises (UKM) in Bringin Village. The isample of this study is 99 respondents taken from the entire population using census sample. In collecting the data, this research uses a Likert scale with 11 indicators. The data analysisi technique used is descriptive analysis, multiple lineari regression analysis. The iresults iof the analysis state that work family conflict iaffects the performance of female employees in UKM Desa Bringin, Juwana District, Pati Regency with a value of 3.530 and a significance value iof 0.001. Workload affects the performance of female employees at UKM Bringin Village, Juwana District, Pati Regency with a value of -5.186 and a isignificance value of i0.000. Work family conflict and workload simultaneously iaffect the performancei of female employees at UKM Bringin Village, Juwana District, Pati Regency as evidenced by the Adjusted R Square value of 0.396. Married femalei employees are expected to be able to balance family roles and work roles and dare to express opinions and complaints not to force themselves to complete work.